Pelaksanaan perbankan Islam di Aceh, Indonesia - Zaini, Muhammad Amin (2018)
The implementation of Islamic banking in Aceh is still minimal compared to conventional banking even though the majority of people in Aceh Province, Indonesia, are Muslims. At the same time, a negative perception has arisen of Islamic banking due to several factors such as lack of information on Islamic banking, excessive profits on financings, profit amount is assumed to be the same as usury, lack of information, limited types of products, limited knowledge of the Syariah system, incomplete facilities and unclear rates of profit distribution. Thus, the study examined the implementation of Islamic banking in Aceh, Indonesia, and the government’s approaches in strengthening the industry. Besides, this study also identified the level of awareness and knowledge of the people of Aceh in accepting Islamic banking and the obstacles faced by Islamic banks and the government of Aceh in the implementation of Islamic banking. The study used the ‘fardhu kifayah’ theory and the stakeholder theory to foothold the study. The qualitative research method was used and deemed appropriate to answer the objectives and research questions. This study found that Islamic banks in Indonesia had made plans to enter the market in Aceh. They also had established many branches in line with the wishes of the majority of the Acehnese that wanted Islamic banking. The study also revealed that the Acehnese have accepted the implementation of Islamic banking despite facing various obstacles during its implementation. The government was supportive with specific acts and regulations. This study recommends that Islamic banks in Aceh need to provide clear guidelines regarding the concepts, strategies, vision (inclusive and consistent) in the effort to improve the awareness and knowledge of the society. Besides, the government should have a clear direction of Islamic banking development and apply several effective initiatives to improve the Islamic banks in Aceh.